A prospective pilot study on DACHAO intervention for improving embryo quality metrics in IVF/ICSI failure cases - Xing, Rui; Jiang, Lei; Zhang, Jie; Zuo, Xiao-Qi; Xu, Xin; Xue, Meng-Chi; Zhao, Yi-Ran; Hao, Gui-Min (Frontiers in Cell and Developmental Biology, 2026)
Research questionEmbryo quality serves as a pivotal determinant in assisted reproductive technology (ART) outcomes, with high-grade embryos correlating with improved pregnancy/live birth rates but poor morphology elevating the risks of implantation failure and pregnancy loss. Despite its clinical significance, therapeutic options for enhancing embryo development remain limited, necessitating novel interventions to improve poor embryogenesis.ObjectiveThis study aimed to evaluate the efficacy of DACHAO Reco18—a formulation containing natural extracts of clove, Sophora flower bud, and yam—in improving reproductive outcomes among IVF patients with a history of poor embryo quality.DesignThis was a prospective self-controlled study, to assess the effects of DACHAO Reco18 containing natural extracts of clove, Sophora flower bud, and yam on reproductive outcomes in 68 IVF patients (aged 20–40 years) with a history of IVF/ICSI failure and documented poor embryo quality (≤20% high-grade embryos and no surplus embryos). All participants had previously undergone IVF/ICSI treatment at our center between January 2022 and December 2023. Over 6 weeks of oral treatment, outcomes were compared between pre- and post-intervention cycle. The primary outcome measure was embryo parameters, while secondary outcomes encompassed oocyte yield, fertilization efficiency, implantation rate and pregnancy rate.ResultsDACHAO Reco18 intervention significantly improved the mean oocyte yield from 7.955 to 8.955 oocytes retrieved per cycle, fertilization outcomes with 2 pronucleus (PN) zygotes increasing from 3.731 to 5.463 embryos, and Day-3 embryo enhancement from 1.896 to 3.000 viable embryos. High-quality embryos surged by 118.52% from 0.567 to 1.239, with the quality rate improving from 30.729% to 44.107%. Additionally, when compared to the pre-treatment cycle, the post-treatment cycle showed statistically significant improvements in the implantation rate (0%–32.00%), biochemical pregnancy (0%–24.00%) and clinical pregnancy (0%–21.05%). Subgroup analyses revealed FSH reduction in hyper-gonadotropic patients (from 12.083 to 9.941 mIU/mL).ConclusionThis prospective self-controlled study suggests that a six-week DACHAO Reco18 intervention is associated with improved ovarian response and embryological outcomes in IVF patients with poor embryo quality, including reduced FSH in hyper-gonadotropic individuals. While promising, these preliminary findings warrant verification through randomized controlled trials to evaluate its potential as an adjuvant treatment in ART.